Treatment of Acid Mine Drainage Through Chemical Precipitation (e92a39e9-acb8-460c-9a0e-44f49dd6a52e) - Carin Laubscher; Francis W. Petersen; Jaap P. Smit (International Mineral Processing Congress, 2003)
Waste streams, such as acid mine drainage, are often characterised by low pH values and high concentrations of heavy metals, dissolved solids, calcium and sulphates. Although lime remediation effectively removes most of the heavy metals as hydroxides, it is less effective at lowering levels of sulphates. Various methods of removing sulphates from effluents exist, such as precipitation with lime, precipitation with barium salts, co-precipitation with calcium carbonate, reverse osmosis, and ion exchange. Mintek developed a chemical precipitation (SAVMIN) process to treat acid mine drainage, which entails the addition of lime to precipitate the metal hydroxides, and the subsequent formation (precipitation) of calcium sulphoaluminate or ettringite. The key to the viability of the new technology lies in the correct use, regeneration and recycling of Al(OH)3 used to precipitate the ettringite. The water produced by this process is suitable for disposal to watercourses or for agricultural, domestic or industrial consumption. No brines are produced as the salts are converted to solid hydroxides, gypsum and calcium carbonate. The technology has been tested on several different waters in pilot plant campaigns. Results obtained indicate that potable water can be produced (containing less than 200 mg/L sulphate and no heavy metals) as long as the monavalent ions (Na+, Cl-, etc.) are within limits.